The classroom teacher's technology survival guide - Johnson, Doug, 1952- (Hoboken, NJ : Jossey-Bass, 2012)
'A comprehensive guide for integrating educational technology in the K-12 classroom.This is a must-have resource for all K-12 teachers and administrators who want to really make the best use of available technologies. Written by Doug Johnson, an expert in educational technology, The Classroom Teacher's Technology Survival Guide is replete with practical tips teachers can easily use to engage their students and make their classrooms places where both students and teachers will enjoy learning. Covers the most up-to-date technologies and how they can best be used in the classroom Includes advice on upgrading time-tested educational strategies using technology Talks about managing'disruptive technologies' in the classroom Includes a wealth of illustrative examples, helpful suggestions, and practical tips This timely book provides a commonsense approach to choosing and using educational technology to enhance learning'--
Introduction -- Chapter one : Why should classroom teachers be technologically skillful? -- Chapter two : Q&A about some basics -- Chapter three : Using technology for professional productivity -- Chapter four : The technology upgrade -- Chapter five : Teaching 1st century skills -- Chapter six : Managing disruptive technologies in the classroom -- Chapter seven : Commonsense practices for safe and ethical technology use -- Chapter eight : Developing a long-term learning strategy -- Chapter nine : Looking into the crystal ball -- Readings and resources.
Includes bibliographical references and index.
Keywords: Educational technology; Education -- Effect of technological innovations on; EDUCATION / Computers & Technology; Informationstechnik; Lehrer; Unterricht; Education -- Effect of technological innovations on; Educational technology